If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3+9x=3(x+6)
We simplify the equation to the form, which is simple to understand
-3+9x=3(x+6)
Reorder the terms in parentheses
-3+9x=+(+3x+18)
Remove unnecessary parentheses
-3+9x=+3x+18
We move all terms containing x to the left and all other terms to the right.
+9x-3x=+18+3
We simplify left and right side of the equation.
+6x=+21
We divide both sides of the equation by 6 to get x.
x=3.5
| 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) | | 3x+14=x+24 | | -3x+1=-5x+17 | | 6=10-x | | 3(x+3)=(4+x) | | 2x+2x-1=12 | | 4Y+20=8 | | -3x+8=-2x+9 | | 10x-7= | | 2(2+2)*3= | | -3x-10=x-6 |